Metody otsiniuvannia materialno-tekhnichnoho zabezpechennia budivelnoho pidpryiemstva v umovakh tsyfrovizatsii - Shevtshuck , K.; Filippov , O.; Ustymenko , A.; Tymofieiev , D. (Ways to Improve Construction Efficiency, 2022)
Material and technical support (MTS) is one of the key components of the construction enterprise management system, since the continuity, rhythm and quality of construction and installation work largely depend on the efficiency of resource supply. In modern conditions, when the construction industry of Ukraine operates under the pressure of external crisis factors - war, energy and logistics risks, rising resource prices - the need to improve the methods for assessing MTS is growing. The article is devoted to the study of existing approaches to assessing the level of provision of an enterprise with material, technical and energy resources, as well as the definition of indicators that allow an objective quantitative and qualitative assessment of the efficiency of logistics, reliability of supplies and the level of readiness of the enterprise to perform production tasks.The paper analyzes and systematizes the methods of evaluating MTZ according to such criteria as: comprehensiveness of provision, timeliness of deliveries, compliance of volumes and quality of resources with project requirements, the degree of use of digital inventory accounting and monitoring systems, the effectiveness of interaction with suppliers. Particular attention is paid to the methods of econometric analysis, multi-criteria evaluation, logistics modeling, as well as the implementation of BIM and ERP systems in the MTZ management process. An integrated evaluation model is proposed that can be used to rank projects by the level of supply risk, forecast shortages and optimize inventories in the supply chain system.The results obtained can be used by construction companies, developers, contracting organizations, as well as logistics and resource management specialists to improve the internal MTZ control system, minimize losses and ensure the stability of production processes in a dynamic external environment.